I2/DMSO mediated multicomponent reaction for the synthesis of 2-arylbenzo[d]imidazo[2, 1-b] thiazole derivatives. Issue 21 (16th May 2019) - Jana, Asim; Bhaumick, Prabhas; Panday, Anoop Kumar; Mishra, Richa; Choudhury, Lokman H.
Abstract : A series of 2-arylbenzo[ d ]imidazo[2, 1- b ] thiazoles tethered with barbituric acid has been prepared using I2 in DMSO medium under conventional or microwave heating conditions. Abstract : Synthesis of a series of 2-arylbenzo[ d ]imidazo[2, 1- b ] thiazoles tethered with barbituric acid moiety has been reported from the three component reaction of 2-aminobenzothiazoles, barbituric acids and terminal aryl acetylenes or aryl methyl ketones in the presence of I2 in DMSO medium. Both conventional and microwave heating conditions can be used for this multicomponent reaction. The salient features of this methodology are: (i) formation of one C–C and two C–N bonds in one-pot under metal-free oxidation followed by cyclization, (ii) selective formation of the fused imidazole ring, (iii) wide substrate scope, (iv) easy purification of the products, (v) products having more than one pharmaceutically important motifs and (vi) gram scale synthesis possible.